A new type of non-deep physiological dormancy: evidence from three annual Asteraceae species in the cold deserts of Central Asia. Issue 4 (December 2014) - Nur, Mihray; Baskin, Carol C.; Lu, Juan J.; Tan, Dun Y.; Baskin, Jerry M.
Abstract Although Asteraceae species are important in the cold deserts of Central Asia, little is known about their seed dormancy and germination. We determined dormancy breaking and germination requirements of three annual Asteraceae, Echinops gmelinii, Epilasia acrolasia and Koelpinia linearis. Achenes (seeds) were tested for germination in light and in darkness over a range of alternating temperatures after various periods of burial outdoors and of dry storage. Germination phenology was monitored for seeds sown in irrigated and non-irrigated sand, and temperature requirements for dormancy break were determined under wet and dry conditions. Effects of pericarp and phyllaries on germination of E. acrolasia and E. gmelinii, respectively, were determined. Low percentages of 20-day-old seeds of E. acrolasia and K. linearis were non-dormant and germinated to low percentages over the range of temperatures, whereas all seeds of E. gmelinii were dormant. As seeds of the three species afterripened, they germinated over the range of temperatures. Whether seeds germinated in autumn or spring depended on the amount of sand moisture. Mechanical resistance of the pericarp and phyllaries reduced germination of E. acrolasia and E. gmelinii, respectively. Temperature requirements for germination as seeds come out of dormancy do not correspond to any of the known five types of non-deep physiological dormancy (PD). Thus, a sixth type is recognized in which germination occurs over the same range of temperatures in the early and late stages of dormancy break. Type 6 allows seeds to germinate at high or at low temperatures, whenever sand moisture is non-limiting.